2018
DOI: 10.1002/jcp.26320
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Effects of mTOR/NF‐κB signaling pathway and high thoracic epidural anesthesia on myocardial ischemia‐reperfusion injury via autophagy in rats

Abstract: We investigated the role of mammalian target of rapamycin/nuclear factor-kappa B (mTOR/NF-κB) signaling pathway in high thoracic epidural anesthesia (HTEA) against myocardial ischemia-reperfusion (I/R) injury in rats. The rat model of myocardial I/R injury was established. Ninety rats were divided into the normal, sham, I/R, eHTEA, the PDTC, and HTEA + PDTC groups. ELISA was applied to detect cardiac function indexes. HE staining was conducted to observe histopathological changes of myocardial tissues, and TTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…(c and d) The expression of adhesion molecules (ICAM-1 and VCAM-1) was detected by WB (e). *p < 0.05, **p < 0.01 Wen, Lin, Wei, & Huang, 2018), myocardial infarction (Maracle et al, 2018) and heart failure (Hu et al, 2018). In our study, our results indicated Gal-3 effect was closely associated with the phosphorylation levels of p65, IKKα, and IKKβ levels, suggesting that Gal-3 may be involved in HUVECs inflammatory reaction on IKK-dependent NF-κB activation.…”
Section: Discussionsupporting
confidence: 57%
“…(c and d) The expression of adhesion molecules (ICAM-1 and VCAM-1) was detected by WB (e). *p < 0.05, **p < 0.01 Wen, Lin, Wei, & Huang, 2018), myocardial infarction (Maracle et al, 2018) and heart failure (Hu et al, 2018). In our study, our results indicated Gal-3 effect was closely associated with the phosphorylation levels of p65, IKKα, and IKKβ levels, suggesting that Gal-3 may be involved in HUVECs inflammatory reaction on IKK-dependent NF-κB activation.…”
Section: Discussionsupporting
confidence: 57%
“…Inhibition of early activation of NfκB may suppress the inflammatory response due to cytokines, thus by reducing the gene expression of intercellular adhesion molecules creates a protective effect on I/R damage . In the study of rat that performed by Huang et al, it was shown that autophagy‐related genes induced by inhibition of NfκB may play a vital role in reducing myocardial I/R injury. Melatonin can reduce the upregulation of various pro‐inflammatory cytokines, such as interleukins and TNFα, by preventing the translocation of NfκB into the nucleus .…”
Section: Discussionmentioning
confidence: 99%
“…A mixture of ketamine (50–75 mg/kg) and xylazine (1–5 mg/kg) induces anesthesia [464], while a single injection of pentobarbital [15–80 mg/kg] is also used [216, 446, 464]. However, in a recent study ketamine/xylazine induced bradycardia and increased serum-free fatty acids, while both ketamine/xylazine and isoflurane induced hyperglycemia.…”
Section: Small Animal Hearts In Situmentioning
confidence: 99%